Sustaining excellence in Islamic tourism through certification - Ruzulan, Zulaipa; Jamaludin, Mohammad Aizat; Saidin, Nurulaina (Akademi Pengajian Islam Kontemporari UiTM, 2024)
Islamic tourism is a significant industry in Malaysia owing to its vast opportunity to boost the Malaysian economy and bring it more excellence worldwide. For this reason, many tourism products and services could be promoted and marketed in this Islamic tourism industry. However, to remain established as an Islamic tourism contributor, the players need more knowledge on the significance of adopting Shariah related standards and certification for their company. Therefore, this paper discusses the urgency of adopting standards and certification in sustaining the Islamic tourism industry. A qualitative research methodology involves using in-text documents to gather data. This study has found that the religious observance, business opportunity, claimant, and governance approach lead to the need to have certification for Islamic tourism products in Malaysia. This study suggests that there is a need for more attention from the government authorities to increase the participation of the players in obtaining the certification. Therefore, the available products offered in the Islamic tourism industry could increase the confidence and trust of the travellers.